STUDENT POLITICS IN URBAN TERNATE, NORTH MALUKU - Amin, Basri (Universitas Negeri Semarang, 2014)
This article examines student politics articulated by university students in contemporary Ternate, North Maluku. The involvement of students in the political arena in the region is mostly organized through regional (ethnic) organizations.The larger context of such political process is decentralisation, which make religional resource Â resources dominated by the state. At the same time competition among local elites and ethnic groups flourish. This is the main background of a new formation of group interests in local level â€“-including local university students– to gain group advantages. The case of Ternate, North Maluku, is an example of how groups of students organize their practical interests in the arena of politics by exploiting youth associations and ethnic organizations.Â Artikel ini mengkaji tentang politik yang diartikulasikan oleh kalangan mahasiswa dalam percaturan politik lokal di Ternate, Maluku Utara. Keterlibatan mahasiswa dalam arena kekuasaan di kawasan ini lebih banyak dilakukan melalui instrumen organisasi kedaerahan (etnis). Konteks besar yang menjadi landasan dari proses sosial ini adalah desentralisasi yang menempatkan sedemikian rupa sumberdaya pembangunan lebih banyak didominasi oleh negara, tapi pada saat yang sama perkembangan politik etnis terus menyertai persaingan kelompok dan elit lokal. Kasus Maluku Utara adalah sebuah contoh bagaimana kaum muda memainkan kepentingannya sendiri dalam percaturan kekuasaan dan dalam hal memanfaatkan kesempatan-kesempatan praktis untuk mereka.